Designing and Validating a Community-Based Palliative Psychological Service Package and Evaluating Its Effectiveness on Pain Perception and Death Anxiety in Patients with Breast Cancer - Sharif Malmir, Mohamad; Seyrafi, Mohammadreza; Zomorodi, Saeedeh (Psychology of Woman Journal, 2026)
Objective: This study aimed to design, validate, and evaluate the effectiveness of a community-based palliative psychological service package on pain perception and death anxiety in patients with breast cancer. Methods and Materials: In the qualitative phase, data were collected through in-depth interviews with 12 women diagnosed with breast cancer and content analysis of 22 related scientific articles. The designed intervention package was then presented to 15 psychology experts, and its validity was confirmed using survey methods and content analysis. In the quantitative phase, the statistical population included women with breast cancer residing in Khorramabad city, who were purposively selected and then randomly assigned to experimental and control groups (15 participants in each group). The research instruments included the McGill Pain Questionnaire (Melzack, 1975) and the Templer Death Anxiety Scale (Templer, 1970), both of which demonstrated appropriate reliability and validity. Data analysis, conducted using SPSS version 26 with repeated measures ANOVA and Bonferroni post-hoc tests. Findings: The findings indicated that the intervention package significantly reduced pain perception and death anxiety in the experimental group. The package, which emphasized mindfulness techniques and emotion management training, effectively contributed to the psychological and social empowerment of the patients. Conclusion: This study highlights the importance of integrating psychological interventions with breast cancer treatments and developing effective community-level palliative care programs.